Symptomatic Lingual Thyroglossal Duct Cyst in Children: A Laryngomalacia Phenotype. (January 2023) - Shumrick, Christopher M.; Calder, Alyssa N.; Vecchiotti, Mark A.; Scott, Andrew R.
Objectives: Patients with lingual thyroglossal duct cyst (TGDC) can present as symptomatic with obstructive airway and feeding difficulties. Methods: We present 3 cases of symptomatic lingual TGDC. Results: All 3 patients were diagnosed with laryngomalacia and underwent further concurrent or delayed airway intervention, in addition to cyst removal. Conclusions: We reason that there is a phenotype of laryngomalacia in the symptomatic lingual thyroglossal duct cyst patients who present with symptoms due to disruption in laryngeal anatomy rather than the cyst itself causing obstructive symptoms. Distinguishing this phenotype, especially in comparison to other pathologies such as vallecular cysts, may better allow for planning of concurrent or delayed airway procedures and overall counseling of parents.